Comparison between single and combined post-treatment with S-Methyl-N, N-diethylthiolcarbamate sulfoxide and taurine following transient focal cerebral ischemia in rat brain. (6th August 2015) - Gharibani, P.; Modi, J.; Menzie, J.; Alexandrescu, A.; Ma, Z.; Tao, R.; Prentice, H.; Wu, J.-Y.
Highlights: Taurine has neuroprotective effect in stroke by reducing apoptosis, ATF6 and IRE-1. DETC-MeSO suppresses endoplasmic reticulum stress-induced apoptosis through PERK. Combined DETC-MeSO and taurine reduce apoptosis and all three ATF6, IRE-1 and PERK. Combined DETC-MeSO and taurine attenuate αII-spectrin, caspase 12 and 3 and gliosis. Abstract: We have recently reported on the efficacy of an N-methyl-d -aspartate (NMDA) receptor partial antagonist, S-Methyl-N, N-diethylthiolcarbamate sulfoxide (DETC-MeSO), in improving outcome following stroke, including reduced infarct size and calcium influx, suppressing the endoplasmic reticulum (ER) stress-induced apoptosis as well as improving behavioral outcome. DETC-MeSO was shown to suppress the protein kinase R-like endoplasmic reticulum kinase (PERK) pathway, one of the major ER stress pathways. Several studies including ours have provided evidence that taurine also has neuroprotective effects through reducing apoptosis and inhibiting activating transcription factor 6 (ATF6) and inositol requiring enzyme 1 (IRE-1) pathways. We hypothesized that a combined treatment with DETC-MeSO and taurine would ameliorate ischemia-induced brain injury by inhibiting all three ER stress pathways. Twenty four hours following reperfusion of a 2-h ischemic stroke, rats received either 0.56-mg/kg DETC-MeSO or 40-mg/kg of taurine, either alone or in combination, subcutaneously for 4 days. Our study showed that combined DETC-MeSO and taurine, but not DETC-MeSO alone at the dose used, greatly reduced the infarct size, improved performance on the neuro-score test and attenuated proteolysis of αII-spectrin. Meanwhile, the level of the pro-apoptotic protein, Bax, declined and the anti-apoptotic protein, B-cell lymphoma 2 (BCL-2), expression was markedly increased. Combination therapy decreased both caspase-12 and caspase-3 activation by preventing the release of Cytochrome-c from mitochondria, indicating attenuation of apoptosis in ischemic infarct. Glucose-regulated protein (GRP)78 as a marker of the unfolded protein response decreased and levels of the key ER stress protein markers p-PERK-ATF4, p-eIF2α and cleaved-ATF-6 were found to significantly decline. NeuN expression levels indicated that more neurons were protected in the presence of DETC-MeSO and taurine. We also showed that combined treatment can prevent gliosis and increase p-AKT a pro-survival marker in the penumbra. Therefore, we conclude that combined treatment with both DETC-MeSO and taurine synergistically inhibits all three ER stress pathways and apoptosis and therefore can be a novel and effective treatment after ischemic stroke.